Short-term Outcome of Oral Prednisolone in the Management of Primary Adhesive Capsulitis. (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the short term outcome of oral Prednisolone in the management of primary adhesive capsulitis in terms of pain relief and improvement in shoulder range of motion.Methods: This descriptive study was carried out in Orthopedic Department District Head Quarter Hospital(DHQ) Teaching Hospital Kohat Development authority(KDA) Kohat from 23rd July 2020 to 23rd December 2021. All adults patients with primary adhesive capsulitis fulfilling the inclusion criteria were treated with 30 mg oral prednisolone in tapering dose for 3 weeks. The intensity of pain was assessed using Visual Analogue Scale(VAS) and shoulder range of motion(ROM) was measured with goniometer at 3 weeks and compared with pre treatment values.Results: In this study 46 patients were included. Female were 28 (60.87%) while males were 18 (39.13%). Average age was 52.35±6.48 years. Non-dominant and dominant shoulders were affected in 27(58.70%) and 19(41.30%) patients respectively. The mean pre treatment VAS significantly improved from 8.23±3.2 to 1.97±1.1 post treatment.(p